An Analysis Of Role Of SIDBI In Facilitating The Growth Of Msmes And Entrepreneurship (Journal of Namibian Studies : History Politics Culture, 2023)
The role of micro, small and medium enterprises (MSMEs) in the growth and upliftment of Indian economy is commendable. MSMEs play a very significant role to promote entrepreneurship and increase employment in any developing nation. But, these enterprises also face some major problems, biggest of them being the financial hurdles. Research has shown that MSMEs face troubles in arranging adequate finance due to unawareness and complicated procedures. To address this issue, Small Industries Development Bank of India (SIDBI) was established on April 2, 1990 under the SIDBI Act, 1989.SIDBI helps in promotion, financing, development and coordination activities. The Indian Government has made it mandatory for SIDBI to be the primary financial institution for MSMEs and to fulfill this mandate; SIDBI has divided its role into five major parts i.e. Indirect Landing, Direct Landing, Fund of Fund, Promotion & Development and Facilitator.This paper is a discussion on the Facilitator role of SIDBI. Under the facilitator part, SIDBI has been assigned the position of Nodal Agency by the government of India for implementing the subsidy related schemes for MSMEs at the root level.The discussion has been done in two parts : (1) In first part, various schemes of SIDBI which have been implemented for MSMEs over the years has been discussed on the basis of the data extracted from government websites and Annual Reports of SIDBI and MSMEs .(2) After that, a comparison has been done for subsidy scheme CLCSS between SIDBI and other assigned banks using Z test to know whether SIDBI plays a significant role in providing financial assistance to MSMEs or not, and the result show that there is a significant difference between the number of beneficiaries of SIDBI as compared to the other ten banks over the period of 7 years I.e. 2015-2022. The data has been collected from authentic secondary sources.